Efektifitas Zakat Produktif Terhadap Pengentasan Tingkat Kemiskinan Studi Kasus BAZNAS Kabupaten Bengkalis - Sri Wahyuningsih (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2020)
This research aims to determine how effective productive zakat is in alleviating poverty levels and targeting accuracy. Then to determine the effect of the empowerment of productive zakat on the recipient of productive zakat from the Bengkalis District National Amil Zakat Board. This research is quantitative and descriptive research. The results of this research found that the development of a business that has been carried out by 100 mustahik recipients of productive zakat has no effect on the social status of the recipient of zakat, this is due to the lack of intensive assistance and the limited knowledge and human resource management, as well as not being targeted in terms of distribution productive zakat. So that the effectiveness of productive zakat on the Bengkalis District National Amil Zakat Board does not significantly influence poverty alleviation.